CASE SERIES: ANTITUBERCULAR THERAPY-INDUCED HEPATITIS - G, SIRISHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Drug-induced liver injury (DILI) accounts for 20–40% of cases of fulminant hepatic failure. Antitubercular therapy (ATT) may cause hepatotoxicity which can range from transient asymptomatic rise in liver enzymes to acute liver failure. The drugs in ATT responsible for hepatotoxicity include isoniazid, rifampicin, and pyrazinamide. Case series was done to present three different cases of ATT-induced hepatotoxicity which came to the Clinical Pharmacology and Therapeutics Department in NIMS for management.